Policy Roles in Promoting Affordable Housing for Survivors of Intimate Partner Violence - Keefe, Rachel (Violence against women, 2021)
Survivors of intimate partner violence (IPV) face housing insecurity when escaping violence. The Violence Against Women Act (VAWA) and Homeless Emergency Assistance and Rapid Transition to Housing (HEARTH) Act policies were put in place to protect this population. This article uses policy analysis to understand the provisions they provide for survivors. The case of a small city will be presented to understand the local implementation of these policies with regard to survivors’ access to affordable housing in tight housing markets. Finally, recommendations will be presented to strengthen the policies to better meet IPV survivors’ housing needs.